Thiosemicarbazide-based iron(III) and manganese(III) complexes. Structural, electrochemical characterization and antioxidant activity - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
New iron(III) and manganese(III) complexes were synthesized by the condensation of 1-phenyl-1, 3-butanedione-S-propyl-thiosemicarbazone (I) with salicylaldehyde in the presence of iron(III) or manganese(II) ions. The complexes were characterised by analytical and spectroscopic methods. X-ray analysis displayed the square pyramidal environments of the iron and manganese ions. The electrochemical behaviors of the iron(III) (1a) and manganese(III) (1b) complexes were studied by cyclic voltammetry and square wave voltammetry in different solvents. Both complexes displayed metal-based electron transfer reactions in addition to ligand based irreversible reduction and oxidation processes, which were affected by the type of metal. Spectroelectrochemical methods were used to examine the electrogenerated species of the complexes and to define the redox processes. The total antioxidant capacity (as the TEAC value) and free radical scavenging activities (FRS%) of the compounds were determined. The TEAC values of 1 (2.78), to (1.63) and 1b (1.28) are higher than those of vitamin C (0.96). (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Thiosemicarbazide; Iron; Manganese; Electrochemistry; Antioxidant; TRANSITION-METAL-COMPLEXES; RAY CRYSTAL-STRUCTURE; NICKEL(II) COMPLEXES; ELECTROCATALYTIC REDUCTION; CYTOTOXIC ACTIVITY; COPPER-COMPLEXES; LIGANDS; FE(III); SALEN; IRON